Pentingnya Pendidikan Agama Bagi Anak Berkebutuhan Khusus - Ardila Pebiani; Cita Genial; Jelita Nur; Kholizah Fitri; Ratu Azmi; Siti Hamidah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Spirituality is a need of every individual in the relationship between God Almighty. Talking about spirituality is closely related to religion and divinity. Religion is a very important thing that plays a major role in providing guidance for life and in religion there is also an order to study for each of His servants regardless of the differences in each individual human being. Children with special needs (ABK) are children who have different characteristics from children in general, therefore several factors that have an influence on the spiritual aspects for children with special needs require assistance from parents, teachers, and a supportive environment to provide religious learning values for the spiritual development of children with special needs. This study uses a qualitative method by collecting data from a literature review which is processed into steps to be implemented for the reader. This study aims to provide some methods used as a medium for learning religion to meet the spiritual needs of children with special needs according to the characters they each have. Such as learning religious concepts for visually impaired, deaf, disabled, disabled, and tunalaras children using appropriate media based on their needs. Religious education is an important component for children with special needs to make them perfect humans who coexist with other humans. God created all His creatures perfectly without exception, whether natural or unnatural, all are His very special gifts.